2017
DOI: 10.1016/j.sleh.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' technology and face-to-face time use predict objective sleep outcomes

Abstract: Objectives The present study examined both within- and between-person associations between adolescents’ time use (technology-based activities and face-to-face interactions with friends and family) and sleep behaviors. We also assessed whether age moderated associations between adolescents’ time use with friends and family and sleep. Design Adolescents wore an actigraph monitor and completed brief evening surveys daily for 3 consecutive days. Participants Adolescents (N = 71; Mean age = 14.50 years old, SD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Brunetti et al (2016), for example, found that computer use doubled the odds of a short night's sleep, while talking on a mobile phone tripled the odds of a short night's sleep 22 . In contrast, Tavernier et al (2017) found that talking on the phone increased the sleep duration, whereas texting reduced the sleep duration. In this study, social media use (e.g.…”
Section: Sleep Durationmentioning
confidence: 80%
See 3 more Smart Citations
“…Brunetti et al (2016), for example, found that computer use doubled the odds of a short night's sleep, while talking on a mobile phone tripled the odds of a short night's sleep 22 . In contrast, Tavernier et al (2017) found that talking on the phone increased the sleep duration, whereas texting reduced the sleep duration. In this study, social media use (e.g.…”
Section: Sleep Durationmentioning
confidence: 80%
“…Of the included studies, 18 were conducted in North America [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] , 23 in Europe , ve in Australia and New Zealand [52][53][54][55][56] , and three studies combined several western countries [57][58][59] . There were three randomized controlled trials (RCTs) 27,28,50 , two quasiexperimental studies 26,51 , 15 prospective cohort studies 12,16,19,24,30,32,35,37,40,42,45,47,48,52,55 , and 29 cross-sectional studies 11, 13-15, 17, 18, 20-23, 25, 29, 31, 33, 34, 36, 38, 39, 41, 43, 44, 46, 49, 53, 54, 56-59 . Detailed descriptions of study design and results are available in Supplementary eTables 2-4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of bedtime technology use has mainly been investigated with self-reported outcome measures and may thereby be prone to misclassification, recall difficulty, recall bias, and response-style bias [ 14 ]. Only a few studies have applied objective sleep measures based on actigraphy and examined the association between sleep and self-reported media use [ 33 , 34 ]. These studies report that self-reported bedtime technology use is negatively related to objective sleep measures in adolescents.…”
Section: Discussionmentioning
confidence: 99%